Efektivitas Konsumsi Kurma Untuk Meningkatkan Kadar Hemoglobin pada Ibu Hamil Trimester III Studi Di PMB “S”, Kecamatan Panekan, Kabupaten Magetan - Sri Wahyuni; Ayesha Hendriana Ngestiningrum; Tutiek Herlina; Astin Nur Hanifah (FORIKES, 2023)
The incidence of anemia in pregnant women at the Panekan Health Center, Magetan during 2021 was 22.89% of pregnant women undergoing integrated antenatal care. Related to pregnancy anemia, dates contain iron of 1.75 mg per 100 grams which has the potential to be utilized. The purpose of this study was to analyze the effectiveness of consuming dates to increase hemoglobin levels in third trimester pregnant women. The design of this study was a pre-test and post-test with a non-equivalent control group. The research subjects were 40 third trimester pregnant women, totaling 40 people at the